2003
DOI: 10.1111/1467-9507.00224
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Social Competence in Elementary School Among Children of Adolescent Mothers

Abstract: This study examined factors related to social competence in first grade among children of low-income, adolescent mothers. The sample included 83 mother-child dyads who had participated in a family support program for adolescent mothers. Characteristics of the child, mother, and the child's living context were examined for their relationship to children's social skills and problem behaviors. Several factors had significant bivariate relationships with social competence. Children with higher social skills and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…As for the social attributes subscale the highest mean was for children of mothers with bachelor's degrees. These results are not surprising but rather provide support to research studies that found positive relations between social competence and social maturity and mothers' education level (Abraham & Christopherson, 1982;Bates, Luster, & Vanderbelt, 2003;Hoglund & Leadbeater, 2004;Namita, 1992;Pushpalata & Singh, 2009). This finding implies that higher levels of education may promote mothers' self-esteem and positive self-regard.…”
Section: Differences Between Kindergarten Children's Individual and Ssupporting
confidence: 80%
“…As for the social attributes subscale the highest mean was for children of mothers with bachelor's degrees. These results are not surprising but rather provide support to research studies that found positive relations between social competence and social maturity and mothers' education level (Abraham & Christopherson, 1982;Bates, Luster, & Vanderbelt, 2003;Hoglund & Leadbeater, 2004;Namita, 1992;Pushpalata & Singh, 2009). This finding implies that higher levels of education may promote mothers' self-esteem and positive self-regard.…”
Section: Differences Between Kindergarten Children's Individual and Ssupporting
confidence: 80%
“…Not all mothers have the personal or external resources to become “super mothers,” and some of our young mothers seemed overwhelmed by their stressful circumstances. Living in a neighborhood with a high concentration of impoverished families is also a significant stressor that is predictive of children's academic success in first grade (Bates, Luster, & Vandenbelt, 2003). Other stressors common to our sample included domestic violence, having an incarcerated partner, and frequent changes of residence.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, residing in dangerous neighborhoods has been linked to more maternal depression (Cutrona et al, 2005; Ross, 2000) and to less nurturing, warm, and supportive parenting (Ceballo & McLoyd, 2002; Duncan, Brooks-Gunn, & Klebanov, 1994; Furstenberg, 1993; Klebanov, Brooks-Gunn, & Duncan, 1994; Mistry et al, 2002). Moreover, during early childhood exposure to neighborhood violence has been directly linked to increases in children’s externalizing (Bates, Luster, & Vandenbelt, 2003; Dodge, Pettit, & Bates, 1994; Greenberg et al, 1999; Linares et al, 2001; Plybon & Kliewer, 2001) and internalizing problems (Linares et al, 2001). The level of neighborhood violence was expected to be directly associated with mothers’ feelings of depression, such that any effects of neighborhood violence on toddler-aged children’s problem behavior would be indirect (see Figure 1, path e).…”
Section: The Family Stress Model and Child Problem Behaviors: A Replimentioning
confidence: 99%